Cultural changes in the late modern period: Understanding the transition from materialistic to post-materialistic values - Vitezović Ivan (Megatrend Revija)
This paper deals with the consideration and perception of cultural changes in the late modern period. It seeks to understand in which way and why the changes occurred, as well as to provide an account of the wider socio-historical context in which the transition from materialist to post-materialist value orientations took place. The results of many empirical studies clearly show this value change at the global level. It started in the 1970s, continued during the 1980s (being further stimulated by social changes such as: the fall of the Berlin Wall, the collapse of communism in Eastern Europe, the emergence of the neoliberal capitalist paradigm at the global level) and continues even in the current age of intense globalization. , networking of society, increased competitiveness on the labor market, etc. Through the presentation of the broader context, this paper seeks to provide a new angle of viewing the studies conducted in this field of research, which has an increasing importance both in the academic context and in the everyday life of people.